Molecular architecture of the Spire-actin nucleus and its implication for actin filament assembly. - Sitar, T.; Gallinger, J.; Ducka, A.M.; Ikonen, T.P.; Wohlhoefler, M.; Schmoller, K.M.; Bausch, A.R.; Joel, P.; Trybus, K.M.; Noegel, A.A.; Schleicher, M.; Huber, R.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
The Spire protein is a multifunctional regulator of actin assembly. We studied the structures and properties of Spire-actin complexes by X-ray scattering, X-ray crystallography, total internal reflection fluorescence microscopy, and actin polymerization assays. We show that Spire-actin complexes in solution assume a unique, longitudinal-like shape, in which Wiskott-Aldrich syndrome protein homology 2 domains (WH2), in an extended configuration, line up actins along the long axis of the core of the Spire-actin particle. In the complex, the kinase noncatalytic C-lobe domain is positioned at the side of the first N-terminal Spire-actin module. In addition, we find that preformed, isolated Spire-actin complexes are very efficient nucleators of polymerization and afterward dissociate from the growing filament. However, under certain conditions, all Spire constructs--even a single WH2 repeat--sequester actin and disrupt existing filaments. This molecular and structural mechanism of actin polymerization by Spire should apply to other actin-binding proteins that contain WH2 domains in tandem.